THE DEVELOPMENT OF STORY BOOK “IKAN SAKTI SUNGAI JANIAH" AS A LEARNING RESOURCE OF LITERATURE AT ELEMENTARY SCHOOL - Suci Amalia; Gustimal Witri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research aims at developing folklore story book of " Ikan Sakti Sungai Janiah" and finding out its feasibility. The story book was designed by using coreldraw7. Model 4D was used as the research method by using four stages; those are define, design, develop and dessiminate, but it was only limited until the third stage. The data of this research was taken from a valid design-expert-instrument, a valid language-expert-instrument and students’ responses. The data was a quantitative data which was measured by using guideline citeria for assessment categories in determining the quality of the product. The research findings based on a design expert on draft 1 with average percentage of 81.4% with feasible category considered improved on draft 2 to 96% with highly feasible category. Furthermore, based on a language expert on draft 1 with the average percentage 68.75% with feasible category, it was considered improved on draft 2 to 95% with highly feasible category. For students’ responses, the average percentage was 94.5% with highly feasible category. Based on the result of the research, it can be concluded that the product developed by the researcher was considered very proper to use as a learning source of literature at primary school.